Post-mortem Characterisation of a Case With an ACTG1 Variant, Agenesis of the Corpus Callosum and Neuronal Heterotopia - Vontell, Regina; Supramaniam, Veena G.; Davidson, Alice; Thornton, Claire; Marnerides, Andreas; Holder-Espinasse, Muriel; Lillis, Suzanne; Yau, Shu; Jansson, Mattias; Hagberg, Henrik E.; Rutherford, Mary A. (Frontiers in Physiology, 2019)
Neuronal heterotopia are ectopic nodules of nerve cells that failed to migrate appropriately during the early development of the fetal brain. Subcortical and periventricular neuronal heterotopia have been described previously in association with agenesis of the corpus callosum (ACC). Most common neuronal migration disorders are related to rare genetic mutations, but in ACC, the genetic basis is unknown in up to 55-70% of cases or is heterogeneous in nature[1]. In this case report, we investigated a neonatal brain with ACC, and neuronal heterotopia (ACC-H) diagnosed on antenatal MR imaging and consistent with band heterotopia on postmortem brain images. Histologically clusters of neurons were seen in both the subcortical and periventricular white matter (PVWM) brain region that coincided with impaired abnormalities in radial glial formation. Immunohistochemistry was performed on paraffin-embedded brain tissue blocks from this case ACC-H and an age-matched control. Using tissue sections from the frontal lobe, we examined the distribution of neuronal cells (HuC/HuD, calretinin, and parvalbumin) growth cone (drebrin) and synaptic proteins (synaptophysin and SNAP-25). Additionally, we investigated how the glia (astroglia; nestin, GFAP, vimentin); oligodendroglia (Olig2) and microglia (Iba-1) differed in ACC-H compared to an age-matched control in the corpus callosum, cortex, lateral ganglionic eminence, and PVWM. As expected in the ACC-H case, we found a lack of callosal radial glia and glutamatergic fibers. We also found a decrease in neurons in the cortical region, disturbances in radial glia and a lack of extracellular matrix components in the ACC-H case. The lateral ganglionic eminence and the PVWM regions in the ACC-H case lacked several cellular components that were identified in the control. Inside the neuronal heterotopia, we found evidence of glutamatergic and GABAergic neurons with apparent synaptic connections. The data presented from this case study provides insight as to the composition of neuronal heterotopia, and how disturbances of important migratory signals may dramatically affect ongoing brain development.